ANALISIS PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI DINAS SUMBER DAYA ALAM DAN BINA MARGA KOTA SURABAYA - Siti Munawaroh (Universitas Jenderal Ahmad Yani, 2026)
Quality public services are the main indicator of the successful implementation of good governance principles in regional government administration. This study aims to analyze in depth the implementation of good governance principles in public services at the Surabaya City Department of Natural Resources and Highways (DSDABM). The principles studied include transparency, accountability, responsiveness, participation, effectiveness, and efficiency. This study uses a qualitative approach with descriptive analytical methods. Data were obtained through interviews, observations, and documentation studies. The results show that the Surabaya City Department of Natural Resources and Highways (DSDABM) has implemented good governance principles through various public service innovations, the use of digital technology, and the strengthening of the public complaint system. However, obstacles still exist in the form of limited human resources, suboptimal public participation, and challenges in cross-sector coordination. This study recommends strengthening institutional capacity and consistent application of good governance principles to improve the quality of public services.